Pemberdayaan Ekonomi Produktif pada Masyarakat Miskin di Wilayah Kelurahan Puruk Cahu Seberang Kabupaten Murung Raya Kalimantan Tengah - Periyadi Periyadi; Abdul Kadir. MS; Junaidi Junaidi; Noorlaily Maulida; Dewi Ariefahnoor; Edy Mahfuz; Muhammad Haris Syafitri (Jurnal Pelayanan Masyarakat, 2025)
Science continues to advance over time. This development has led to the birth of various new technologies that mark the progress of the times. Currently, technology has entered the digital era, where almost all areas of life are beginning to utilize these advances to increase work efficiency and effectiveness. In Indonesia, digital transformation has also penetrated various sectors, including education. This change presents a significant opportunity for the world of education to expand access, improve the quality of learning, and encourage innovation in teaching methods. As an entity closely linked to human culture and civilization, education has undergone significant changes in the era of globalization. The use of digital technologies, such as online learning, learning management systems (LMS), and interactive media, has become an integral part of the educational process. This not only facilitates the delivery of material but also opens up more flexible and inclusive learning opportunities for various levels of society. However, behind these opportunities, challenges also arise, such as disparities in technology access, low digital literacy in some communities, and the need to adapt curricula and teaching methods to be relevant to current developments. Therefore, the success of educational transformation in the digital era depends not only on the availability of technology but also on the readiness of human resources, including educators and students, to optimize its use. Therefore, the development of digital science and technology has become a driving force for global educational change. Education is required to adapt quickly and accurately to produce a generation that is not only academically intelligent.